Stroheim - Lennig, Arthur (University Press of Kentucky, 2000)
Erich von Stroheim (1885-1957) was one of the giants in American film history. Stubborn, arrogant, and colorful, he saw himself as a cinema artist, which led to conflicts with producers and studio executives who complained about the inflated budgets and extraordinary length of his films. Stroheim achieved great notoriety and success, but he was so uncompromising that he turned his triumph into failure. He was banned from ever directing again and spent his remaining years as an actor. Stroheim's life has been wreathed in myths, many of his own devising. Arthur Lennig scoured European and Americ.